Diseño y simulación estructural de una escalera abatible de plataforma (2020)
This is a study that applies the methodology of the mechanical design process and makes use of simulation with design software as a support tool to carry out the structural evaluation of the new innovative "folding" design of an airplane-type platform ladder. These stairs in their traditional airplane-type design are not folding and are shaped as a set of fixed assembly with wheels to be transported, due to their high height it prevents the ladder from being used in all kinds of spaces and requiring a special storage site, for which establishes the modification in the design and functionality characteristics for storage and transport. The ladder is designed and a kinematic and kinetic analysis of the design is made. Also, specialized software is used to perform finite element analysis that allows validating the deformation conditions and the stress levels that the ladder supports, all framed in compliance with the standard to guarantee, safety, resistance and compliance with all aspects related to the mechanical design of the new ladder as a folding structural element, maintaining the necessary resistance conditions for a functional, safe and reliable model that allows the worker to reach a height of 5 meters and that can also be transported from safely once it is in a horizontal position.